Composite calcium carbonate powder for rubber and preparation method thereof
By preparing composite calcium carbonate powder, reacting with materials such as dipotassium hydrogen phosphate, sodium hydroxide and modified nano calcium carbonate coatings, forming layer-coated composite calcium carbonate powder, solving the problem of poor uniformity of calcium carbonate and rubber, and achieving improved mechanical properties and enhanced cross-linking density of rubber.
Patent Information
- Application Number
- CN202411808588.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
In the prior art, the compound uniformity of calcium carbonate and rubber is poor, resulting in insufficient reinforcement effect on rubber properties, and the single application of nanofillers cannot meet the improvement of rubber properties requirements.
By preparing composite calcium carbonate powder, it is used to react with materials such as dipotassium hydrogen phosphate, sodium hydroxide and modified nano calcium carbonate coatings, combined with ultrasonic dispersion and click reaction techniques, layer-coated composite calcium carbonate powder is formed to improve its compatibility with rubber and cross-linking density.
The uniform dispersion and efficient reinforcement of composite calcium carbonate powder in rubber is achieved, the mechanical properties and cross-linking density of rubber are improved, and the rubber properties are improved.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rubber preparation, and in particular relates to composite calcium carbonate powder for rubber and a preparation method thereof. Background Art
[0002] Calcium carbonate is widely used in the field of polymer filling and reinforcement due to its easy availability, low price, low toxicity, low pollution, high whiteness, large filling amount and good mixing and processing performance. The rubber field is an important field of application of inorganic filler calcium carbonate, but ordinary calcium carbonate can only act as a filler due to its large particle size and poor compatibility with rubber. Direct blending with rubber materials is likely to affect the performance of rubber materials. It is usually blended with rubber under the condition of a coupling agent, which is not only costly and complicated in process, but also silane coupling agents will release volatile organic compounds, causing environmental pollution. In the prior art, inorganic nanofillers with smaller particle sizes, such as nano calcium carbonate, are usually used, and the surface modification of the nanofiller is adopted to enhance the compatibility between the nanofiller and the rubber, so as to improve the performance of the rubber. However, with the continuous improvement of the requirements for rubber properties, a single type of inorganic nanofiller can no longer meet the demand.
[0003] Patent CN117417576A discloses a nanofiller for reinforcing a rubber composite material and a preparation method thereof, wherein the nanofiller is obtained by respectively modifying carbon nanotubes and nano-calcium carbonate and then grinding and mixing them with ammonium salts; however, in this solution, the modified carbon nanotubes, modified nano-calcium carbonate and amine salts are ground and mixed, and the degree of mixing is greatly affected by the grinding, and uneven mixing is easily caused, thereby reducing the reinforcing ability of the nanofiller on the rubber. Summary of the invention
[0004] The purpose of the present invention is to solve the problem of how to improve the composite uniformity of calcium carbonate and other rubber fillers and enhance the reinforcing effect of the composite fillers on rubber properties, and to provide a composite calcium carbonate powder for rubber and a preparation method thereof.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A method for preparing composite calcium carbonate powder for rubber comprises the following steps:
[0007] Step 1, dissolving dipotassium hydrogen phosphate in deionized water in a reaction kettle, adding 1M sodium hydroxide solution to adjust the pH value to 6-6.5, adding the modified nano-calcium carbonate coating, adding 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide after ultrasonic dispersion, stirring and activating for 2-3 hours, and then filtering, mixing the filtered solid with thiolated chitosan in deionized water, adjusting the pH value to 8-8.5 with 1M sodium hydroxide solution, stirring and reacting for 10-12 hours, filtering, and vacuum drying the precipitate to obtain a composite nano-calcium carbonate coating;
[0008] Step 2: ultrasonically disperse the composite nano-calcium carbonate coating in deionized water in a beaker, drop a 1M methacrylic acid aqueous solution into a 1M sodium hydroxide aqueous solution, and then drop it into a reactor to stir and react for 1-2 hours, then filter to obtain a precipitate, and ultrasonically disperse the precipitate again in a 1M sodium hydroxide aqueous solution to obtain a 3-4w / v% precipitate dispersion, drop a 0.5M aluminum chloride aqueous solution into the precipitate dispersion under ice bath conditions, stir and react for 1-2 hours, filter, wash with a 70wt% ethanol solution, and vacuum dry to obtain a composite calcium carbonate powder.
[0009] Furthermore, in step 1, the usage ratio of dipotassium hydrogen phosphate, deionized water, modified nano-calcium carbonate coating, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide is 6-8g:500-600mL:5-8g:1-2g:0.8-1g; the usage ratio of the thiolated chitosan and deionized water is 5-7g:500-700mL.
[0010] Furthermore, the modified nano calcium carbonate coating is prepared by the following steps:
[0011] In a reaction kettle, carboxymethyl cellulose is added to an acetic acid aqueous solution with a volume fraction of 2%, heated to 50-60° C. and stirred until the carboxymethyl cellulose is dissolved, the nano-calcium carbonate coating is added, ultrasonic dispersion is performed for 10-15 minutes, glyoxal is added, heated to 50-60° C. and stirred for reaction for 30-40 minutes, filtered, washed, and vacuum dried to obtain a modified nano-calcium carbonate coating.
[0012] Furthermore, the usage ratio of carboxymethyl cellulose, acetic acid aqueous solution, nano-calcium carbonate coating and glyoxal is 10-15g:400-500mL:5-10g:5-6mg.
[0013] Furthermore, the nano calcium carbonate coating is prepared by the following steps:
[0014] In a reaction kettle, 85 wt% ethanol aqueous solution and 25 wt% ammonia water are mixed, nano calcium carbonate and tetraethyl orthosilicate are added, and the mixture is stirred at 200-300 rpm for reaction for 20-24 hours. After filtering and washing the precipitate, the nano calcium carbonate coating is obtained by vacuum drying.
[0015] Furthermore, the usage ratio of ethanol aqueous solution, ammonia water, nano-calcium carbonate and tetraethyl orthosilicate is 600-900 mL: 15-25 mL: 8-12 g: 30-40 mL.
[0016] Further, the thiolated chitosan is prepared by the following steps:
[0017] Dissolve chitosan in deionized water in a reactor, add glacial acetic acid, stir the reaction for 3-4 hours, then add 2-iminothiolane hydrochloride, add 5M sodium hydroxide solution dropwise into the reactor to adjust the pH value to 6-6.5, stir the reaction for 20-24 hours, then put it into a dialysis bag, dialyze it with dilute hydrochloric acid, and freeze-dry it after dialysis to obtain thiolated chitosan.
[0018] Furthermore, the usage ratio of chitosan, deionized water, glacial acetic acid and 2-iminothiolane hydrochloride is 8-10 g: 1-1.2 L: 20-25 mL: 0.3-0.4 g.
[0019] Furthermore, in step 2, the usage ratio of the composite nano-calcium carbonate coating, deionized water, methacrylic acid aqueous solution and sodium hydroxide aqueous solution is 5-8g: 150-200mL: 8-10mL: 150-200mL; the usage ratio of the precipitation dispersion and the aluminum chloride aqueous solution is 150-200mL: 200-250mL.
[0020] Beneficial effects of the present invention:
[0021] (1) The composite calcium carbonate powder prepared by the present invention has a uniform composite degree and a good reinforcing effect on rubber. By composite silicon dioxide, carboxymethyl cellulose and mercapto chitosan on the nano-calcium carbonate matrix, not only the agglomeration of the nano-calcium carbonate is reduced, but also the reaction grafting ability of the nano-calcium carbonate coated with silicon dioxide is improved. The composite calcium carbonate powder formed by layer-by-layer coating has rich surface groups, which improves the crosslinking density between the composite calcium carbonate powder and the rubber material, has a high degree of dispersion in the rubber, and has a good improvement on the mechanical properties of the rubber.
[0022] (2) The preparation method of the present invention comprises the following steps: a nano-calcium carbonate coating formed by nano-calcium carbonate and silicon dioxide is coated with mercapto chitosan under the cross-linking action of carboxymethyl cellulose, and mercapto chitosan is grafted with methacrylic acid through a click reaction to form a layer-by-layer coated composite calcium carbonate powder. The composite calcium carbonate powder is based on nano-calcium carbonate, has a small particle size, and has high mechanical strength. The aluminum methacrylate on the surface of the composite calcium carbonate powder can also serve as a reactive filler to cross-link with molecules in the rubber to generate ionic bonds, thereby increasing the cross-linking density of the rubber material. The chitosan contained in the composite calcium carbonate powder can also prevent the migration of antioxidants during the rubber mixing process, thereby improving the performance of the rubber. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Embodiment 1: A method for preparing composite calcium carbonate powder for rubber, comprising the following steps:
[0025] Step 1: Mix 600 mL of 85 wt% ethanol aqueous solution and 15 mL of 25 wt% ammonia water in a reactor, add 8 g of nano-calcium carbonate and 30 mL of ethyl orthosilicate, stir and react at 200 rpm for 20 h, filter and wash the precipitate with ethanol and deionized water, and vacuum dry at 50° C. for 12 h to obtain a nano-calcium carbonate coating.
[0026] Step 2: In a reaction kettle, add 10 g of carboxymethyl cellulose to 400 mL of 2% acetic acid aqueous solution, heat to 50° C. and stir until the carboxymethyl cellulose is dissolved, add 5 g of nano-calcium carbonate coating, ultrasonically disperse for 10 min, add 5 mg of glyoxal, heat to 50° C. and stir for 30 min, filter, wash the precipitate with anhydrous ethanol and deionized water, and vacuum dry at 50° C. for 12 h to obtain a modified nano-calcium carbonate coating.
[0027] Step 3: Dissolve 8 g of chitosan in 1 L of deionized water in a reactor, add 20 mL of glacial acetic acid, stir and react for 3 h, then add 0.3 g of 2-iminothiolane hydrochloride, add 5 M sodium hydroxide solution dropwise into the reactor to adjust the pH value to 6, stir and react for 20 h, then put into a dialysis bag, dialyze with 5 mM dilute hydrochloric acid solution, 5 mM dilute hydrochloric acid solution containing 1 wt % and 1 mM dilute hydrochloric acid, and freeze-dry after dialysis to obtain thiolated chitosan.
[0028] Step 4: Dissolve 6 g of dipotassium hydrogen phosphate in 500 mL of deionized water in a reactor, add 1 M sodium hydroxide solution to adjust the pH value to 6, add 5 g of modified nano-calcium carbonate coating, add 1 g of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and 0.8 g of N-hydroxysuccinimide after ultrasonic dispersion, stir and activate for 2 hours, and then filter. Mix the filtered solid with 5 g of thiolated chitosan in 500 mL of deionized water, adjust the pH value to 8 with 1 M sodium hydroxide solution, stir and react for 10 hours, filter, and vacuum dry the precipitate at 40° C. for 12 hours to obtain a composite nano-calcium carbonate coating.
[0029] Step 5: Ultrasonic disperse 5 g of the composite nano-calcium carbonate coating in 150 mL of deionized water in a beaker, drop 8 mL of 1 M methacrylic acid aqueous solution into 150 mL of 1 M sodium hydroxide aqueous solution, and then add it dropwise to the reactor to stir and react for 1 h, then filter to obtain a precipitate, and ultrasonically disperse the precipitate in 1 M sodium hydroxide aqueous solution to obtain a 3 w / v % precipitate dispersion, add 200 mL of 0.5 M aluminum chloride aqueous solution to 150 mL of the precipitate dispersion under ice bath conditions, stir and react for 1 h, filter, wash with 70 wt % ethanol solution, and vacuum dry at 50 ° C for 6 h to obtain a composite calcium carbonate powder.
[0030] Embodiment 2: A method for preparing composite calcium carbonate powder for rubber, comprising the following steps:
[0031] Step 1: Mix 750 mL of 85 wt% ethanol aqueous solution and 20 mL of 25 wt% ammonia water in a reactor, add 10 g of nano-calcium carbonate and 35 mL of ethyl orthosilicate, stir and react at 250 rpm for 22 h, filter and wash the precipitate with ethanol and deionized water, and vacuum dry at 55° C. for 14 h to obtain a nano-calcium carbonate coating.
[0032] Step 2: In a reaction kettle, 12.5 g of carboxymethyl cellulose was added to 450 mL of 2% acetic acid aqueous solution, heated to 55° C. and stirred until the carboxymethyl cellulose was dissolved, 7.5 g of the nano-calcium carbonate coating was added, ultrasonic dispersion was performed for 12.5 min, 5.5 mg of glyoxal was added, heated to 55° C. and stirred for reaction for 35 min, filtered, the precipitate was washed with anhydrous ethanol and deionized water, and vacuum dried at 55° C. for 14 h to obtain a modified nano-calcium carbonate coating.
[0033] Step 3: Dissolve 9 g of chitosan in 1.1 L of deionized water in a reactor, add 22.5 mL of glacial acetic acid, stir and react for 3.5 h, then add 0.35 g of 2-iminothiolane hydrochloride, add 5 M sodium hydroxide solution dropwise into the reactor to adjust the pH value to 6.3, stir and react for 22 h, then put into a dialysis bag, dialyze with 5 mM dilute hydrochloric acid solution, 5 mM dilute hydrochloric acid solution containing 1 wt % and 1 mM dilute hydrochloric acid, and freeze-dry after dialysis to obtain thiolated chitosan.
[0034] Step 4: Dissolve 7 g of potassium dihydrogen phosphate in 550 mL of deionized water in a reactor, add 1 M sodium hydroxide solution to adjust the pH value to 6.3, add 6.5 g of modified nano-calcium carbonate coating, add 1.5 g of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and 0.9 g of N-hydroxysuccinimide after ultrasonic dispersion, stir and activate for 2.5 h, and then filter. Mix the filtered solid with 6 g of thiolated chitosan in 600 mL of deionized water, adjust the pH value to 8.3 with 1 M sodium hydroxide solution, stir and react for 11 h, filter, and vacuum dry the precipitate at 45 ° C for 14 h to obtain a composite nano-calcium carbonate coating.
[0035] Step 5: ultrasonically disperse 6.5 g of the composite nano-calcium carbonate coating in 175 mL of deionized water in a beaker, drop 9 mL of a 1 M methacrylic acid aqueous solution into a 175 mL 1 M sodium hydroxide aqueous solution, and then drop it into a reactor and stir for 1.5 h, then filter to obtain a precipitate, ultrasonically disperse the precipitate in a 1 M sodium hydroxide aqueous solution to obtain a 3.5 w / v% precipitate dispersion, drop 225 mL of a 0.5 M aluminum chloride aqueous solution into the 175 mL precipitate dispersion under ice bath conditions, stir for 1.5 h, filter, wash with a 70 wt % ethanol solution, and vacuum dry at 55 ° C for 7 h to obtain a composite calcium carbonate powder.
[0036] Embodiment 3: A method for preparing composite calcium carbonate powder for rubber, comprising the following steps:
[0037] Step 1: Mix 900 mL of 85 wt% ethanol aqueous solution and 25 mL of 25 wt% ammonia water in a reactor, add 12 g of nano-calcium carbonate and 40 mL of ethyl orthosilicate, stir and react at 300 rpm for 24 h, filter and wash the precipitate with ethanol and deionized water, and vacuum dry at 60° C. for 16 h to obtain a nano-calcium carbonate coating.
[0038] Silicon dioxide is coated on the surface of nano-CaCO3 by the sol-gel method, and tetraethyl orthosilicate is hydrolyzed into Si(OH)4 in the solution to generate polysiloxane monomers or oligomers which are polymerized to form polysiloxane, which is homogenized in an ethanol aqueous solution and adsorbed on the surface of nano-calcium carbonate to coat the nano-calcium carbonate.
[0039] Step 2: In a reaction kettle, add 15 g of carboxymethyl cellulose to 500 mL of 2% acetic acid aqueous solution, heat to 60° C. and stir until the carboxymethyl cellulose is dissolved, add 10 g of nano-calcium carbonate coating, ultrasonically disperse for 15 min, add 6 mg of glyoxal, heat to 60° C. and stir to react for 40 min, filter, wash the precipitate with anhydrous ethanol and deionized water, and vacuum dry at 60° C. for 16 h to obtain a modified nano-calcium carbonate coating.
[0040] The nano-calcium carbonate coating is placed in a carboxymethyl cellulose solution under the cross-linking action of glyoxal, and the carboxymethyl cellulose molecules are grafted onto the silicon dioxide on the surface of the nano-calcium carbonate coating by the reaction of aldehyde groups and hydroxyls to obtain a nano-calcium carbonate coating with surface grafted carboxymethyl cellulose.
[0041] Step 3: Dissolve 10 g of chitosan in 1.2 L of deionized water in a reactor, add 25 mL of glacial acetic acid, stir for 4 h, then add 0.4 g of 2-iminothiolane hydrochloride, dropwise add 5 M sodium hydroxide solution to the reactor to adjust the pH value to 6.5, stir for 24 h, then put into a dialysis bag, dialyze with 5 mM dilute hydrochloric acid solution, 5 mM dilute hydrochloric acid solution containing 1 wt % and 1 mM dilute hydrochloric acid, and freeze-dry after dialysis to obtain thiolated chitosan.
[0042] Step 4: Dissolve 8 g of dipotassium hydrogen phosphate in 600 mL of deionized water in a reactor, add 1 M sodium hydroxide solution to adjust the pH value to 6.5, add 8 g of modified nano-calcium carbonate coating, add 2 g of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and 1 g of N-hydroxysuccinimide after ultrasonic dispersion, stir and activate for 3 hours, and then filter. Mix the filtered solid with 7 g of thiolated chitosan in 700 mL of deionized water, adjust the pH value to 8.5 with 1 M sodium hydroxide solution, stir and react for 12 hours, filter, and vacuum dry the precipitate at 50° C. for 16 hours to obtain a composite nano-calcium carbonate coating.
[0043] The carboxyl groups in the carboxymethyl cellulose in the modified nano-calcium carbonate coating are activated with 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride in a phosphate buffer solution, and then cross-linked with the thiol groups in the thiolated chitosan to coat the thiolated chitosan on the surface of the modified nano-calcium carbonate to obtain a composite nano-calcium carbonate coating containing thiol groups on the surface.
[0044] Step 5: ultrasonically disperse 8 g of the composite nano-calcium carbonate coating in 200 mL of deionized water in a beaker, drop 10 mL of a 1 M methacrylic acid aqueous solution into a 200 mL 1 M sodium hydroxide aqueous solution, and then drop it into a reactor and stir for 2 h, then filter to obtain a precipitate, ultrasonically disperse the precipitate in a 1 M sodium hydroxide aqueous solution to obtain a 4 w / v% precipitate dispersion, drop 250 mL of a 0.5 M aluminum chloride aqueous solution into the 200 mL precipitate dispersion under ice bath conditions, stir for 2 h, filter, wash with a 70 wt % ethanol solution, and vacuum dry at 60 ° C for 8 h to obtain a composite calcium carbonate powder.
[0045] The thiol groups on the surface of composite nano-calcium carbonate react with the olefin groups in methacrylic acid to make methacrylic acid grafted on the surface of composite nano-calcium carbonate, and then methacrylic acid reacts with aluminum chloride under alkaline conditions to generate aluminum methacrylate, which can be used as a reactive filler to cross-link with molecules in rubber to generate ionic bonds, thereby increasing the cross-linking density of rubber materials and improving the mechanical properties of rubber; the composite calcium carbonate powder also contains chitosan, and the active amino groups and active hydroxyl groups on the surface of chitosan will react with the surface groups of the antioxidant during the mixing process, fixing the antioxidant on the surface of the composite calcium carbonate powder and reducing the migration of the antioxidant in the rubber, because there are amino and amide groups on the chitosan structure. The NH bonds of these active groups will undergo asymmetric ion splitting under the action of heat or other substances during the vulcanization process to generate ionic groups, thereby participating in the cross-linking reaction of rubber macromolecules, increasing the cross-linking activity of rubber macromolecules, and thus improving the mechanical properties of rubber.
[0046] Comparative Example 1: The difference from Example 1 is that the modified nano-calcium carbonate coating is replaced by a nano-calcium carbonate coating.
[0047] Comparative Example 2: The difference from Example 1 is that the composite nano-calcium carbonate coating is replaced by a nano-calcium carbonate coating.
[0048] Comparative Example 3: The composite nano-calcium carbonate coating in Example 1.
[0049] The sources of some reagents in the embodiments and comparative examples are as follows:
[0050] Nano-calcium carbonate and N-hydroxysuccinimide were purchased from MacLean Reagent Co., Ltd.
[0051] Chitosan was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0052] Carboxymethyl cellulose was purchased from Anhui Zhonghong Bioengineering Co., Ltd.
[0053] Tethyl orthosilicate, acetic acid, glyoxal, ethanol, 2-iminothiolane hydrochloride, dipotassium hydrogen phosphate, methacrylic acid and aluminum chloride were all purchased from Sigma-Aldrich.
[0054] 1-Ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride was purchased from Meryer Co., Ltd (China).
[0055] The composite calcium carbonate powder obtained in Examples 1 to 3 and Comparative Examples 1 to 3 was used as a filler and mixed with EPDM rubber to obtain a rubber sample. The mixing step of the rubber was as follows: after the EPDM raw rubber was thinned 8 times on a rubber mixing mill at room temperature, zinc oxide, stearic acid, composite calcium carbonate powder, antioxidant, accelerator CBS and vulcanizing agent sulfur were added in sequence in a mass ratio of 100:5:2:30:2:2:2, and after mixing evenly, thinly passed through a sheet to obtain a rubber mixture. At room temperature, the rubber mixture was allowed to stand for 12 hours, and then the rubber mixture was hot-pressed and vulcanized at 160° C. using a flat vulcanizer to obtain a rubber sample. The rubber sample was tested for tensile properties according to standard GB / T 528-2009, and for tear strength according to standard GB / T 529-2009. The results are shown in Table 1:
[0056] Table 1
[0057] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Tensile strength(Mpa) 53.4 53.8 53.9 45.3 41.5 47.2 Elongation at break (%) 689.3 692.5 693.7 612.4 574.6 647.1 Tear strength (kN / m) 146.1 149.6 150.2 129.4 118.5 133.9
[0058] As can be seen from Table 1, the composite calcium carbonate powder for rubber prepared by the present invention has a good reinforcing effect on rubber, and the inorganic filler and reactive filler in the composite calcium carbonate improve the mechanical properties and crosslinking density of the rubber, so that the obtained rubber material has excellent performance; Comparative Example 1 does not use carboxymethyl cellulose to modify the nano-calcium carbonate coating, and the surface of the nano-calcium carbonate coating has fewer reactive groups with thiolated chitosan, and has only a small amount of physical adsorption and crosslinking with thiolated chitosan, resulting in fewer thiol groups on the surface of the composite nano-calcium carbonate coating, and a low degree of crosslinking with methacrylic acid. The composite degree of calcium carbonate powder is low, the synergistic reinforcement effect on rubber is low, and the obtained rubber material performance is poor; in Comparative Example 2, since the surface of the nano-calcium carbonate coating does not contain mercapto groups, it cannot form a cross-linking chemical bond with methacrylic acid, and the obtained composite calcium carbonate powder is a powder obtained by physically mixing the nano-calcium carbonate coating and aluminum methacrylate, and the reinforcement effect on rubber is poor; in Comparative Example 3, since there is no reinforcing cross-linking effect of aluminum methacrylate on rubber, the obtained rubber performance is poor, indicating that aluminum methacrylate and composite calcium carbonate powder can produce a synergistic reinforcement effect on rubber, and have better reinforcement ability for rubber.
[0059] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0060] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing composite calcium carbonate powder for rubber, characterized in that: The steps include: Step 1, dissolving dipotassium hydrogen phosphate in deionized water in a reaction kettle, adding 1M sodium hydroxide solution to adjust the pH value to 6-6.5, adding the modified nano-calcium carbonate coating, adding 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide after ultrasonic dispersion, stirring and activating for 2-3 hours, and then filtering, mixing the filtered solid with thiolated chitosan in deionized water, adjusting the pH value to 8-8.5 with 1M sodium hydroxide solution, stirring and reacting for 10-12 hours, filtering, and vacuum drying the precipitate to obtain a composite nano-calcium carbonate coating; Step 2: ultrasonically disperse the composite nano-calcium carbonate coating in deionized water in a beaker, drop a 1M methacrylic acid aqueous solution into a 1M sodium hydroxide aqueous solution, and then drop it into a reactor to stir and react for 1-2 hours, then filter to obtain a precipitate, and ultrasonically disperse the precipitate again in a 1M sodium hydroxide aqueous solution to obtain a 3-4w / v% precipitate dispersion, drop a 0.5M aluminum chloride aqueous solution into the precipitate dispersion under ice bath conditions, stir and react for 1-2 hours, filter, wash with a 70wt% ethanol solution, and vacuum dry to obtain a composite calcium carbonate powder.
2. The method for preparing a composite calcium carbonate powder for rubber according to claim 1, characterized in that: In step 1, the usage ratio of dipotassium hydrogen phosphate, deionized water, modified nano-calcium carbonate coating, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide is 6-8g:500-600mL:5-8g:1-2g:0.8-1g; the usage ratio of thiolated chitosan and deionized water is 5-7g:500-700mL.
3. The method for preparing a composite calcium carbonate powder for rubber according to claim 2, characterized in that: The modified nano calcium carbonate coating is prepared by the following steps: In a reaction kettle, carboxymethyl cellulose is added to an acetic acid aqueous solution with a volume fraction of 2%, heated to 50-60° C. and stirred until the carboxymethyl cellulose is dissolved, the nano-calcium carbonate coating is added, ultrasonic dispersion is performed for 10-15 minutes, glyoxal is added, heated to 50-60° C. and stirred for reaction for 30-40 minutes, filtered, washed, and vacuum dried to obtain a modified nano-calcium carbonate coating.
4. The method for preparing a composite calcium carbonate powder for rubber according to claim 3, characterized in that: The dosage ratio of the carboxymethyl cellulose, the acetic acid aqueous solution, the nano-calcium carbonate coating and glyoxal is 10-15g: 400-500mL: 5-10g: 5-6mg.
5. The method for preparing composite calcium carbonate powder for rubber according to claim 4, characterized in that: The nano calcium carbonate coating is prepared by the following steps: In a reaction kettle, 85 wt% ethanol aqueous solution and 25 wt% ammonia water are mixed, nano calcium carbonate and tetraethyl orthosilicate are added, and the mixture is stirred at 200-300 rpm for reaction for 20-24 hours. After filtering and washing the precipitate, the nano calcium carbonate coating is obtained by vacuum drying.
6. The method for preparing composite calcium carbonate powder for rubber according to claim 5, characterized in that: The usage ratio of the ethanol aqueous solution, ammonia water, nano calcium carbonate and tetraethyl orthosilicate is 600-900 mL: 15-25 mL: 8-12 g: 30-40 mL.
7. The method for preparing composite calcium carbonate powder for rubber according to claim 2, characterized in that: The thiolated chitosan is prepared by the following steps: Dissolve chitosan in deionized water in a reactor, add glacial acetic acid, stir the reaction for 3-4 hours, then add 2-iminothiolane hydrochloride, add 5M sodium hydroxide solution dropwise into the reactor to adjust the pH value to 6-6.5, stir the reaction for 20-24 hours, then put it into a dialysis bag, dialyze it with dilute hydrochloric acid, and freeze-dry it after dialysis to obtain thiolated chitosan.
8. The method for preparing composite calcium carbonate powder for rubber according to claim 7, characterized in that: The usage ratio of the chitosan, deionized water, glacial acetic acid and 2-iminothiolane hydrochloride is 8-10 g: 1-1.2 L: 20-25 mL: 0.3-0.4 g.
9. The method for preparing composite calcium carbonate powder for rubber according to claim 1, characterized in that: In step 2, the usage ratio of the composite nano-calcium carbonate coating, deionized water, methacrylic acid aqueous solution and sodium hydroxide aqueous solution is 5-8g: 150-200mL: 8-10mL: 150-200mL; the usage ratio of the precipitation dispersion and aluminum chloride aqueous solution is 150-200mL: 200-250mL.
10. A composite calcium carbonate powder for rubber, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing polypeptide-grafted chitosan / hydroxyapatite / pearl powder bracket
CN104031288A
Surface modified nano calcium carbonate with core-shell structure and preparation method thereof
CN104559327A
Modified calcium carbonate and application thereof to preparation of silicon rubber
CN108752981A
Preparation method of calcium carbonate-silicon dioxide composite powder
CN109422287A
Preparation method of targeted photo-thermal nanocomposite based on oxidized graphene
CN110302378A